Rekonstruksi Formulasi Historical Approach In Islamic Studies: Islam Sebagai Produk Sejarah dan Sasaran Penelitian - Muh Rizwan Azzahidi (CENDEKIA: Jurnal Studi Keislaman, 2022)
Islam develops and interacts with various new cultures, the problems it faces become more and more complicated. As a result, Islamic studies are not enough with text analysis but also pay attention to the historical aspects that lie behind it. This paper aims to answer the problem of the study of Islamic epistemology which initially rested on idealism which was only textual based to use a contextual approach. The research method used is literature study, which is a series of research that has data sources from books, articles related to the theme. Understanding history in Islamic studies is an effort to find out the reality in the past related to Islamic teachings which are the benchmark for the future era as an effort to anticipate future distortions. The historical approach in Islamic studies has contributed to the value of human life by providing moral messages indirectly contained in history as an effort to anticipate negative thinking patterns in life caused by advances in science.